Factors Influencing The Intention of Businesses Actor To Adopt Online Applications: An Empirical Evidence In Indonesia - Dedy Afrizal; Sunariya Utama; H. Hildawati; Y. Yuhardi; S. Sofyan (Golden Ratio of Marketing and Applied Psychology of Business, 2023)
The use of technology is prevalent in both the public and private sectors. The use of technology in different community activities, of course, has an impact on the community's economic worth. The usage of many current apps makes it a viable alternative for strengthening the community's economy, particularly for micro, small, and medium-sized business actors (UMKM). The purpose of this research is to determine factors influencing the intention of UMKM actors in using accessible applications to sell their products. It is envisaged that by combining the Unified Theory of Acceptance and Use of Technology (UTAUT) theory with various more factors, it will be possible to understand the intentions of business actors toward applications. The results are obtained by using a quantitative approach that uses SEM PLS analysis sourced from respondent's answer data obtained through the distribution of questionnaires to UMKM actors, where Facilitating Condition and Trust is an important construct to consider in seeing the intentions of business actors in using an application. This is hoped that the findings of this study will serve as a reference for the government and private sector in developing policies aimed at increasing the use of applications and encouraging micro, small, and medium business actors to adopt and use online applications, which will undoubtedly help improve the Indonesian people's economy.